Exploring transmedia journalism in the digital age - Gambarato, Renira Rampazzo; Alzamora, Geane (Information Science Reference, 2018)
"This book explores how to tell pervasive news stories across multiple platforms and formats, using current digital technologies, expanding the content and engaging audiences. It presents analytical views on transmedia journalism case studies and the applications and implications of technological advancements, such as virtual reality, social media networks and big data in the journalism realm"--